La lettera rubata e la decostruzione della storia. Derrida tra Heidegger, Lacan e Patočka - Mollisi, Matteo (Bollettino Filosofico, 2021)
The aim of this paper is to grasp some theoretical and ethical implications of the way in which Derrida, in particular in the two confrontations with Lacan and Patočka respectively at the heart of The Purveyor of Truth and The Gift of Death, appropriates the image of the “purloined letter” of E.A. Poe. This will appear closely connected to an absolutely central directive in the complex of Derrida’s path: the deconstruction, carried out by Derrida also by means of a conceptuality of psychoanalytic inspiration, of a metaphysical concept of “history” in favor of an originary “historicity”. Going back to the course on Heidegger held by Derrida in 1964-1965, we will show how the real stake of this plot lies in the way he inherits the Heideggerian “logic” of the unity of dissimulation and disclosure that both Lacan and Patočka associate with the image of the purloined letter. Keywords: Derrida, Heidegger, History, Lacan, Patočka